Management of frontal sinus trauma: a retrospective study of surgical interventions and complications - InKyeong Kim; Jeong-Mo Kim; Jiha Kim; Seung Jin Lee; Eui-Cheol Nam (SpringerOpen, 2024)
Abstract Background Frontal sinus injuries are relatively rare among facial bone traumas. Without proper treatment, they can lead to fatal intracranial complications, including meningitis or brain abscesses, as well as aesthetic and functional sequelae. The management of frontal sinus injuries remains controversial, with various treatment methods and outcomes being reported. This article describes the clinical characteristics, surgical methods, and outcomes among 17 patients who underwent surgery for frontal sinus injury and related complications. Case presentation We retrospectively included 17 patients who underwent surgery for frontal sinus injury and its related complications at the Kangwon National University Hospital between July 2010 and September 2021. Among them, six underwent simple open reduction and fixation of the anterior wall, eight underwent sinus obliteration, and three underwent cranialization. Two patients who underwent sinus obliteration died due to infection-related complications. The patient who underwent cranialization reported experiencing chronic headache and expressed dissatisfaction regarding the esthetic outcomes of the forehead. Except for these three patients, the other patients achieved satisfactory esthetic and functional recovery. Conclusion Active surgical management of frontal sinus injuries is often required owing to the various complications caused by these injuries; however, several factors, including the fracture type, clinical presentation, related craniomaxillofacial injury, and medical history, should be considered while formulating the treatment plan. Surgical treatment through the opening of the frontal sinus should be actively considered in patients with severely damaged posterior wall fractures and those at risk of developing infection.